India : Report on the Observance of Standards and Codes (ROSC)-Data Module. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
A summary of India's dissemination practices relative to the special data dissemination standard (SDDS) is provided. This report is based on the information provided by Indian authorities and data users prior to and during a staff mission from May 13-30, 2002, as well as publicly available information. The assessment of India's data dissemination practices against the SDDS is also provided. A summary assessment of the quality of the principal macroeconomic datasets is also discussed. Finally, the report sets out recommendations to achieve further improvements in India's statistics.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet